Hyper-Interleukin-6 Protects Against Renal Ischemic-Reperfusion Injury—A Mouse Model - Zuaiter, Mohammad; Axelrod, Jonathan H.; Pizov, Galina; Gofrit, Ofer N. (Frontiers in Surgery, 2021)
Background: Most of the ischemia-reperfusion injury (IRI) occurs during reperfusion and is mediated by the immune system. In this study we determined whether immunomodulation with hyper-Interleukin-6 (a recombinant designer cytokine composed of interleukin-6 linked to its soluble receptor) is protective against IRI in mice kidneys. Methods: Hyper-Interleukin-6 (HIL-6) was administered by in vivo plasmid DNA transfection to ten male mice. Twenty-four hours later, unilateral nephrectomy was done. IRI immediately followed by closure of the remaining kidney vascular pedicle for 40 minutes. Seven mice transfected with non-coding control plasmid served as the control group. The functional and morphological effects of IRI and its effect on mice longevity were explored. This was done by serial blood tests and by histopathology done upon sacrifice of the animals at post-operative day 7. Findings: Mice pretreated with HIL-6 had a mean creatinine level at post-operative day 1 of 35.45±4.03 micromole/l and mean Urea level was 14.18±2.69 mmol/l, whereas mean creatinine was 89.33± 69.27 micromole/l (P = 0.025), and mean urea was 38.17±20.77 mmol/l (P = 0.0024) in the control group. Histological changes in the control group included inflammatory infiltration, tubular damage and architectural distortion. These were not seen in the treatment group. Seven days post-operatively the survival rate of treated mice was 100% compared to 50% in the control group (P=0.015). Interpretation: In this single kidney mouse model, pretreatment with HIL-6 administration effectively protected against IRI both morphologically and functionally. Further studies are needed to better understand the mechanism and feasibility of using this immunomodulator.